ChemInform Abstract: An Enantioselective Synthesis of Spirobilactams Through Copper‐Catalyzed Intramolecular Double N‐Arylation and Phase Separation. Issue 4 (January 2016) - Liu, Jianguang; Tian, Yingying; Shi, Jialing; Zhang, Shasha; Cai, Qian
Abstract: A series of title compounds is prepared as building blocks for functional chiral molecules.